Sustainable Futures: Pertamina’s Commitment in Advancing Sustainable Development Goals 13 - Yulia Sari Jimmy, Indah (Universitas Muhammadiyah Tapanuli Selatan, 2024)
This paper examines Indonesia's national energy corporation, Pertamina, and its multimodal strategy for addressing climate change, assessing its efficacy and suitability as a template for other energy corporations. Using a qualitative approach, the research analyzes Pertamina's sustainability reports, news stories, and official documents, focusing on measurable activities and achievements in emission reduction, resource management, and renewable energy integration. Pertamina's commitment to the environment is evident in its comprehensive strategy, which has led to a 31% reduction in greenhouse gas emissions since 2010 and a 5.65 million MWh gain in energy efficiency. The company's initiatives also include the development of 349 Green Energy Stations and significant efforts in water conservation and waste reduction. Pertamina's sustainable materials usage, particularly in packaging, further underscores its environmental responsibility. This study presents Pertamina's approach as an exemplary model for other corporations aiming to integrate sustainability into their operations.Key words: Climate Action, Pertamina, Sustainable Development Goals.